Proteomic Signature of Neuroblastoma Cells UKF-NB-4 Reveals Key Role of Lysosomal Sequestration and the Proteasome Complex in Acquiring Chemoresistance to Cisplatin - Merlos Rodrigo, Miguel Angel; Buchtelova, Hana; de Los Rios, Vivian; Casal, José Ignacio; Eckschlager, Tomas; Hrabeta, Jan; Belhajová, Marie; Heger, Zbynek; Adam, Vojtech (Journal of proteome research, 2019)
Cisplatin (CDDP) is a widely used agent in the treatment of neuroblastoma. Unfortunately, the development of acquired chemoresistance limits its clinical use. To gain a detailed understanding of the mechanisms underlying the development of such chemoresistance, we comparatively analyzed established cisplatin-resistant neuroblastoma cell line (UKF-NB-4CDDP) and its sensitive counterpart (UKF-NB-4). First, using viability screenings, we confirmed the decreased sensitivity of tested cells to cisplatin and identified a cross-resistance to carboplatin and oxaliplatin. Then, the proteomic signatures were analyzed using nano liquid chromatography with tandem mass spectrometry. Among the proteins responsible for UKF-NB-4CDDP chemoresistance, ion channels transport family proteins, ATP-binding cassette superfamily proteins (ATP = adenosine triphosphate), solute carrier-mediated trans-membrane transporters, proteasome complex subunits, and V-ATPases were identified. Moreover, we detected markedly higher proteasome activity in UKF-NB-4CDDP cells and a remarkable lysosomal enrichment that can be inhibited by bafilomycin A to sensitize UKF-NB-4CDDP to CDDP. Our results indicate that lysosomal sequestration and proteasome activity may be one of the key mechanisms responsible for intrinsic chemoresistance of neuroblastoma to CDDP.
Keywords: Apoptosis; Lysosomes; neuroblastom; proliferace buněk; Humans; cisplatina; lidé; Drug Resistance, Neoplasm; Proteasome Endopeptidase Complex; Cisplatin; proteasomový endopeptidasový komplex; chemorezistence; Transcriptome; Neuroblastoma; lyzozomy; Cell Proliferation; Gene Expression Regulation, Neoplastic; proteomika; Cell Line, Tumor; nádorové buněčné linie; transkriptom; regulace genové exprese u nádorů; Proteomics; apoptóza